Konstruksi Standar Kecantikan di Media Sosial dan Dampaknya terhadap Persepsi Diri Mahasiswi - Carelina Ephifania Siagian; Florensya Angelica Delarosa Zalukhu; Zairindra Anggun Safitri; Viero Varbi Sununianti; Istiqoma Istiqoma; Deni Aries Kurniawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The development of social media has brought significant changes in how individuals perceive themselves, especially among female university students who are in the stage of identity formation. Social media is not only used as a communication tool but also as a space that presents homogeneous beauty standards which can influence self-perception. This study aims to analyze the construction of beauty standards on social media and their impact on female students’ self-perception. The research uses a qualitative approach with a literature review method by analyzing 20  relevant academic articles published between 2020 and 2025. Data analysis was conducted using descriptive qualitative techniques, including data reduction, data presentation, and conclusion drawing. The results show that beauty standards on social media are constructed through repeated visual representations and reinforced by algorithmic systems, creating an idealized image of beauty. This condition encourages female students to engage in social comparison, leading to self-dissatisfaction and decreased self-confidence. However, these effects vary depending on individuals’ ability to filter and interpret information. This study highlights the importance of developing critical awareness in social media use to avoid being influenced by unrealistic beauty standards.